Produksi Menurut Yusuf Qardhawi (Studi Literatur Kitab Daurul Qiyam wal Akhlaq fil Iqtishadil Islami) - Muhammad Irwin Muslimin; Nurul Huda (Jurnal Ilmiah Ekonomi Islam, 2022)
The economic system in the modern era can be differentiated into two, conventional economics and Islamic economics. The background of this research is there are differences in the production concept between the two systems. This difference must be studied more deeply, including the thoughts of economists. This study uses a qualitative method which is a library research approach, and the technique used in this study is content analysis.This study explains the production conception that was conveyed by Yusuf Qardhawi in a book called Daurul Wiyam wal Akhlaq fil Iqtishadil Islami. The result of this research is Yusuf Qardhawi explains the concept of production in Islam and divides it into five chapters: (1) the attention of al-Qur'an to natural resources, (2) work is the main joint of production, (3) production in halal chain, (4) protection of natural resources,(5) production targets. The author of this study concludes that Islamic economic thought according to the book Daurul Qiyam wal Akhlaq fil Iqtishadil Islami by Yusuf Qardhawi can explain the conception of production in an Islamic perspective and can also help Muslims understand the concept and application of Islamic production in general.